Myeloablative versus reduced intensity allogeneic stem cell transplantation for relapsed/refractory Hodgkin's lymphoma in recent years: a retrospective analysis of the Lymphoma Working Party of the European Group for Blood and Marrow Transplantation - Genadieva-Stavrik, Sonja; Boumendil, A.; Dreger, Peter; Peggs, K.; Briones, J.; Corradini, P.; Bacigalupo, A.; Socié, G.; Bonifazi, F.; Finel, H.; Velardi, A.; Potter, M.; et al. (Annals of oncology, 2016)
BACKGROUND: To evaluate long-term outcome of myeloablative allogeneic stem cell transplantation (allo-SCT) (MAC) versus reduced-intensity allo-SCT (RIC) in patients with relapsed/refractory Hodgkin's lymphoma (HL) in recent years. - PATIENTS AND METHODS: A total of 312 patients (63 MAC and 249 RIC) with relapsed/refractory HL who received allo-SCT between 2006 and 2010 and were reported to the EBMT Database were included in the study. - RESULTS: With a median follow-up for alive patients of 56 (26-73) months, there were no significant differences in non-relapse mortality (NRM) between MAC and RIC. Relapse rate (RR) was somewhat lower in the MAC group (41% versus 52% at 24 months, P = 0.16). This lower RR translated into a marginal improvement in event-free survival (EFS) for the MAC group (48% versus 36% at 24 months, P = 0.09) with no significant differences in overall survival (73% for MAC and 62% for RIC at 24 months, P = 0.13). Multivariate analysis after adjusting for disease status at the time of allo-SCT showed that the use of MAC was of borderline statistical significance for predicting a lower RR and EFS [HR 0.7, 95% CI (0.5-1.0), P = 0.1] and [HR 0.7, 95% CI (0.5-1.0), P = 0.07], respectively, after allo-SCT. - CONCLUSIONS: With modern transplant practices, the NRM associated with MAC for HL has strongly decreased, resulting into non-significant improvement of EFS because of a somewhat better disease control compared with RIC transplants. The intensity of conditioning regimens should be considered when designing individual allo-SCT strategies or clinical trials in patients with relapsed/refractory HL.
Gesehen am 02.06.2020